The Analysis of Corporate Crime in Indonesia’s Intellectual Property Laws - Aditya Weriansyah; Alvin Prima Ramadani (Global Legal Review, 2022)
White-collar crime is a type of crime that involves a large number of individuals, is carried out in a structured, large-scale manner, and results in significantly greater losses than conventional crimes. Given the growing number of organizations, the potential for white-collar crime is currently reasonably high. Corporations are able to commit various crimes, particularly those motivated by profit, such as infringements on intellectual property rights. Given that many of today's intellectual property rights holders are corporations, corporations and intellectual property rights have a strong link. This is understandable given that firms have more resources and cash to invest in developing new products that can be protected by intellectual property rights. As a result of the tight relationship between intellectual property rights and corporations, the government must be aware of potential intellectual property rights violations committed by corporations. This article aims to see if the current set of intellectual property rights legislation can handle corporate crimes. The method employed in this research is a normative juridical method with a statutory approach to produce clear findings from the formulation of corporate crime under intellectual property rights regulations. The study's findings demonstrate how unprepared existing clusters of intellectual property regulations are to deal with prospective corporate criminal activities. The criteria and system of corporate responsibility, as well as alternative consequences for firms, are pretty minimum in these numerous statutes, starting with the framing of the issue of punishment. As a result, based on vicarious liability theory and the corporate culture model, this article proposes that corporations be recognized as punishable entities under all laws controlling intellectual property rights and the establishment of firm standards and corporate obligations. In addition, this study offers suggestions for the types and amounts of punishments that might be appropriate for corporations.